Alternative splicing derived invertebrate variable lymphocyte receptor displays diversity and specificity in immune system of crab Eriocheir sinensis - Xu, Yuanfeng; Yang, Yanan; Zheng, Jinbin; Cui, Zhaoxia (Frontiers in Immunology, 2023)
Variable lymphocyte receptors (VLRs) play vital roles in adaptive immune system of agnathan vertebrates. In the present study, we first discover a novel VLR gene, VLR2, from an invertebrate, the Chinese mitten crab, Eriocheir sinensis. VLR2 has ten different isoforms formed via alternative splicing, which is different from that in agnathan vertebrates with the assembly of LRR modules. The longest isoform, VLR2-L, responds to Gram-positive bacteria Staphylococcus aureus challenge specifically, while shows no response to Gram-negative bacteria Vibrio parahaemolyticus challenge, confirmed by recombinant expression and bacterial binding experiments. Interestingly, VLR2s with short LRRs regions (VLR2-S8 and VLR2-S9) tend to bind to Gram-negative bacteria rather than Gram-positive bacteria. Antibacterial activity assay proves six isoforms of VLR2 have pluralistic antibacterial effects on bacteria which were never reported in invertebrates. These results suggest that the diversity and specificity of VLR2 resulted from alternative splicing and the length of the LRRs region. This pathogen-binding receptor diversity will lay the foundation for the study of immune priming. Furthermore, studying the immune function of VLR2 will provide a new insight into the disease control strategy of crustacean culture.